2004
DOI: 10.1103/physreve.69.036121
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from antipersistent to persistent behavior in time series possessing the generalyzed dynamic scaling law

Abstract: The behavior of crude oil price volatility is analyzed within a conceptual framework of kinetic roughening of growing interfaces. We find that the persistent long-horizon volatilities satisfy the Family-Viscek dynamic scaling ansatz, whereas the mean-reverting in time short horizon volatilities obey the generalized scaling law with continuously varying scaling exponents. Furthermore we find that the crossover from antipersistent to persistent behavior is accompanied by a change in the type of volatility distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…40 A common property of natural dynamic systems is the Scaling Invariance, which means that the central moments of first, second, third, and fourth order remain asymptotically constant in space and time. This phenomenon, called auto-affinity, is manifested in the time series if they are represented, in the first instance, in time intervals with decreasing duration, and it is observed that their appearance was similar.…”
Section: Scaling Invariance Degreementioning
confidence: 99%
See 1 more Smart Citation
“…40 A common property of natural dynamic systems is the Scaling Invariance, which means that the central moments of first, second, third, and fourth order remain asymptotically constant in space and time. This phenomenon, called auto-affinity, is manifested in the time series if they are represented, in the first instance, in time intervals with decreasing duration, and it is observed that their appearance was similar.…”
Section: Scaling Invariance Degreementioning
confidence: 99%
“…The study of the variables and the interactions of a dynamic system through time focuses on finding patterns, structures, critical points of stability or instability, as well as the initial conditions sensibility to change, to achieve a certain degree of control. 40 A common property of natural dynamic systems is the Scaling Invariance, which means that the central moments of first, second, third, and fourth order remain asymptotically constant in space and time. 41 Generally, every real complex system exhibits scale invariance, that is, its behavior does not change by the rescaling of the variables that govern its dynamics.…”
Section: Scaling Invariance Degreementioning
confidence: 99%
“…Many statistical properties of financial markets have already been explored, and have revealed striking similarities between price volatility dynamics and the kinetic roughening of growing interfaces ( Figure 5). Based on this fact, (Balankin et al, 2004) the general dynamic scaling approach has been used to study the scaling properties of crude oil market.…”
Section: Fractals In Sciencesmentioning
confidence: 99%
“…[5,16]. It was found that both time series behave randomly with exponentially decaying auto-correlation function, whereas their fluctuations exhibit long-range power-law correlations.…”
mentioning
confidence: 99%